Heart or heart-lung transplantation for patients with congenital heart disease in England. Issue 8 (12th January 2019) - Dimopoulos, Konstantinos; Muthiah, Kavitha; Alonso-Gonzalez, Rafael; Banner, Nicholas Robert; Wort, Stephen J; Swan, Lorna; Constantine, Andrew Harry; Gatzoulis, Michael A; Diller, Gerhard Paul; Kempny, Aleksander
Abstract : Background: Increased longevity in patients with congenital heart disease (CHD) is associated with late complications, mainly heart failure, which may not be amenable to redo surgery and become refractory to medical therapy and so, trigger referral for transplantation. We assessed the current role and future prospects of heart and heart-lung transplantation for patients with CHD in England. Methods: We performed a retrospective analysis of hospital episodes for England for 1997–2015, identifying patients with a CHD code (ICD-10 'Q2xx.x'), who underwent heart or heart-lung transplantation. Results: In total, 469 transplants (82.2% heart and 17.8% heart-lung) were performed in 444 patients. Half of patients transplanted had mild or moderate CHD complexity, this percentage increased with time (p=0.001). While overall, more transplantations were performed over the years, the proportion of heart-lung transplants declined (p<0.0001), whereas the proportion of transplants performed in adults remained static. Mortality was high during the first year, especially after heart-lung transplantation, but remained relatively low thereafter. Older age and heart-lung transplantation were strong predictors of death. While an increase in CHD transplants is anticipated, actual numbers in England seem to lag behind the increase in CHD patients with advanced heart failure. Conclusions: The current and future predicted increase in the numbers of CHD transplants does not appear to parallel the expansion of the CHD population, especially in adults. Further investment and changes in policy should be made to enhance the number of donors and increase CHD transplant capacity to address the increasing numbers of potential CHD recipients and optimise transplantation outcomes in this growing population.